Ecological analyses and case-control studies of gastric cancer and leukaemia in relation to DBCP in drinking water in Fresno County, California. Issue 8 (August 1989) - Wong, O; Morgan, R W; Whorton, M D; Gordon, N; Kheifets, L
Abstract : Through ecological analyses and case-control studies, the possible relation of gastric cancer and leukaemia to dibromochloropropane (DBCP) contamination of drinking water in Fresno County, California, has been examined. The ecological analyses examined the correlation between gastric cancer and leukaemia (including the lymphatic varieties), mortality rates, and DBCP concentrations in drinking water by census tract in Fresno County, 1960-83. No correlation was found between gastric cancer or leukaemia and DBCP. The gastric cancer case-control study consisted of 263 deaths from gastric cancer in the county, 1975 to mid-1984, and 1044 controls, using information on residential history and occupation of both cases and controls. Analyses were based on residence at death, as well as one and ten years before death. The case-control study did not find any relation between gastric cancer and DBCP in drinking water. Hispanics in the county were found to experience a relative risk of gastric cancer of 2.77, compared with non-Hispanics. A similar case-control study consisting of 259 cases of leukaemia and 1161 controls found no relation between all leukaemia or lymphatic leukaemia and DBCP in drinking water. Farm workers, however, do appear to have an increased risk of leukaemia.